Guinea-Bissau: 30 years of militarized democratization (1991–2021) - Jaló, Sumaila (Frontiers in Political Science, 2023)
In Guinea-Bissau, democracy replaced a one-party dictatorship regime exercised by the African Party of Independence of Guinea and Cape Verde for 18 years. However, the governing powers have still not abandoned all authoritarian practices of the replaced regime, even three decades after the beginning of democratization process, as attested by the results of the present study. The power of the armed forces to determine the course of governance, more than democratically elected political representatives, is one example. The study qualitatively analyzes this complex sociopolitical context marked by coups d'état and military violence during the thirty years of democratization (1991–2021) using press sources, international organizations documents, and bibliographies. The discussion demonstrates how the armed forces held the real power in Guinea-Bissau and how dangerous is this reality to the democratization, in a country where political organizations, actors, and the military do not distance themselves from one another in the subversion of the democratic order.